2013
DOI: 10.1371/journal.pone.0080501
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Binding Affinity of Therapeutic Monoclonal Antibodies towards Their Native Unpurified Antigens in Human Serum

Abstract: Monoclonal antibodies (mAbs) are a growing segment of therapeutics, yet their in vitro characterization remains challenging. While it is essential that a therapeutic mAb recognizes the native, physiologically occurring epitope, the generation and selection of mAbs often rely on the use of purified recombinant versions of the antigen that may display non-native epitopes. Here, we present a method to measure both, the binding affinity of a therapeutic mAb towards its native unpurified antigen in human serum, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…Analytes were prepared by buffer-exchanging them into the running buffer using spin columns and their "active" or "effective" concentrations determined under conditions of mass transport limitation using a CFCA method on a Biacore T200, as described elsewhere. 38 CFCA experiments confirmed that all analytes used herein were >70% active relative to their nominal or total protein concentration as determined by light absorbance at 280 nm with use of an appropriate extinction coefficient. All kinetic and affinity calculations used active analyte concentrations, rather than nominal ones, as input values.…”
Section: Methodssupporting
confidence: 54%
“…Analytes were prepared by buffer-exchanging them into the running buffer using spin columns and their "active" or "effective" concentrations determined under conditions of mass transport limitation using a CFCA method on a Biacore T200, as described elsewhere. 38 CFCA experiments confirmed that all analytes used herein were >70% active relative to their nominal or total protein concentration as determined by light absorbance at 280 nm with use of an appropriate extinction coefficient. All kinetic and affinity calculations used active analyte concentrations, rather than nominal ones, as input values.…”
Section: Methodssupporting
confidence: 54%
“…Serum experiments were performed as described previously [15, 16] using a Dylight-labeled anti-PGRN mAb 27D5 (M14) as secondary detection, chosen because its epitope does not overlap with that of mAb 14C7 (M4) or mAb 28H6 (M27).…”
Section: Methodsmentioning
confidence: 99%
“…Cell wall glycan-directed Abs are an elegant alternative for the identification of plant cell carbohydrates (Moller et al, 2008;Pattathil et al, 2010;Pedersen et al, 2012). Monoclonal Abs (mAbs) can bind to their epitopes with high selectivity and affinity (K d ;10 -6 M; Müller-Loennies et al, 2000;Bee et al, 2013) and are therefore highly sensitive, specific, and efficient probes. The latter aspect is of paramount importance when the quantity of the sample is severely limited, such as in the caseof endomembrane vesicles.…”
Section: Introductionmentioning
confidence: 99%